Schaum's outline of theory and problems of trigonometry : with calculator-based solutions - Ayres, Frank Jr. (NEW YORK : McGraw Hill Education, 1990)
In revising this book, the strengths of the first edition were retained while reflecting the changes in the study of trigonometry since the first edition was written. This edition focuses entirely on plane trigonometry, deemphasizes the use of logarithms, includes the use of calculator and provides a summary of geometry properties and theorems that are helpful in solving trigonometry problems.
CHAPTER 1. ANGLES AND APPLICATIONS -- CHAPTER 2. TRIGONOMETRIC FUNCTIONS OF A GENERAL ANGLE -- CHAPTER 3. TRIGONOMETRIC FUNCTIONS OF AN ACUTE ANGLES -- CHAPTER 4. SOLUTION OF RIGHT TRIANGLES -- CHAPTER 5. PRACTICAL APPLICATIONS -- CHAPTER 6. APPLYING LOGARITHMS TO TRIGONOMETRY -- CHAPTER 7. REDUCTION TO FUNCTIONS OF POSITIVE ACUTE ANGLES -- CHAPTER 8. VARIATIONS AND GRAPHS OF THE TRIGONOMETRIC -- CHAPTER 9. BASIC RELATIONSHIP AND IDENTITIES -- CHAPTER 10.TRIGONOMETRIC FUNCTIONS OF TWO ANGLES -- CHAPTER 11. SUM,DIFFERENCE AND PRODUCT FORMULAS -- CHAPTE R 12. OBLIQUE TRIANGLES -- CHAPTER 13. AREA OF TRIANGLE -- CHAPTER 14. INVERSE OF TRIGONOMETRIC FUNCTIONS -- CHAPTER 15. TRIGONOMETRIC EQUATIONS -- CHAPTER 16. COMPLEX NUMBERS .
Includes index.